IMPLEMENTASI KEBIJAKAN PERIZINAN RITEL MODERN DI KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI TAHUN 2021 - Rahmi Khairiyah ME; Tito Handoko (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to determine the implementation of modern retail licensing policies in Kuantan Tengah District, Kuantan Singingi Regency, and to determine the impact of the implementation of modern retail licensing policies in Kuantan Singingi Regency. The theory used is the theory of Vera Rimbawani S. (2020), namely the legal basis for issuing permits known as the principle of validity, including: Authority, Substance, and Procedure. The research approach used in this study is a qualitative approach. The location of the research related to the analysis of the modern shop arrangement policy in Kuansing Singingi Regency is the One Stop Integrated Service and Manpower Investment Service. The types of data used in this study are primary data and secondary data. Data collection techniques include interviews, observations, literature studies, and documentation. Data analysis techniques used are qualitative data analysis techniques. The results showed that the basis of the analysis carried out in structuring the retail industry was Presidential Regulation No. 112/2007 and Minister of Trade Regulation No. 53/2008. Through this regulation, the government imposes various restrictions on modern retail businesses, which is also an effort to maintain a balance and healthy business between the two retailers. Modern retail licenses in Kuantan Tengah District are issued by the Office of Investment, One-Stop Integrated Services and Manpower through a Modern Store Business License (IUTM). However, there are still modern retailers that have not yet obtained a Modern Store Business License (IUTM). The impact of the modern retail licensing political policy in Kuantan Singingi Regency is the threat of small businesses in the community around retail stores. Keyword: Implementation, Policy, Licensing, Modern Retail